Prevalence and Risk Factors Associated with Organ Complications in Patients with COVID-19 Admitted to the Intensive Care Unit: A Cohort Study - Piroozeh Taheri; Mohammad Taghi Beig Mohammadi; Mostafa Mohammadi; Atabak Najafi; Samrand Fattah Ghazi; Hesam Aldin Varpaei (Archives of Anesthesia and Critical Care)
Background: Exploring risk factors for the development of COVID-19 in vital organs of the body is necessary to improve patient survival and reduce disability and morbidity due to disease progression. By identifying these underlying risk factors and controlling them, it is possible to prevent extra-pulmonary involvement and even alleviate pulmonary involvement in patients, resulting in a significant reduction in mortality and morbidity rates. This study aimed to identify the underlying risk factors associated with pulmonary and extrapulmonary organ complications of COVID-19. Methods: This study was a cross-sectional descriptive-analytical study. Patients with a definitive diagnosis of COVID-19 who were admitted to the intensive care unit of Imam Khomeini Hospital in Tehran due to respiratory distress and poor clinical condition were included in the study population and were clinically followed up on. Patients' information was collected by reviewing patients' records and the hospital information system. Results: A total of 123 patients were included in the study (63.4% were male, mean age = 58.87 ± 12.37). Using ROC curve analysis, the calculated risk score is considered statistically significant for diagnostic accuracy (AUC = 0.862 [0.797–0.927], P value < value<0.001). A risk score cutoff greater than 1.5 (sensitivity 89.9%, specificity 38.9%) favors an increased likelihood of in-hospital mortality. According to multiple linear regression (F (9,93).369, P value=0.001), chronic obstructive pulmonary disease, asthma, diabetes, SOFA score on days 2 & 3, and ventilation support were predictors of ICU length of stay. Conclusion: A history of chronic heart failure with renal impairment, liver cirrhosis with liver complication, and any underlying disease are associated with pulmonary complications in COVID-19 patients.